2016
DOI: 10.1177/1548051816665582
|View full text |Cite
|
Sign up to set email alerts
|

We May Be Different, but I Can Help You

Abstract: Based on a resource perspective, the authors investigated how leader-follower power distance value incongruence influences employees' withdrawal behavior. Data were collected twice in China, and the sample included 66 leaders and 350 followers. Leader-follower power distance value incongruence was found to be associated with the psychological workplace strain experienced by followers, indicating that incongruence was a stressor for this group and further influenced their withdrawal behavior. Moreover, incongru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…No effects on the other dependent variables were found. This research hence shows that higher value similarity can indeed cause more positive perceptions and motivations towards others, a finding broadly consistent with seminal evidence showing that higher value similarity causes a reduction in prejudice (Rokeach & Mezei, 1966;Stein et al, 1965), higher organisational commitment (Bai et al, 2017), and organisational identification (Edwards & Cable, 2009).…”
Section: Causal Effects Of Value Similaritysupporting
confidence: 89%
“…No effects on the other dependent variables were found. This research hence shows that higher value similarity can indeed cause more positive perceptions and motivations towards others, a finding broadly consistent with seminal evidence showing that higher value similarity causes a reduction in prejudice (Rokeach & Mezei, 1966;Stein et al, 1965), higher organisational commitment (Bai et al, 2017), and organisational identification (Edwards & Cable, 2009).…”
Section: Causal Effects Of Value Similaritysupporting
confidence: 89%
“…Studies focusing on value incongruence suggest that this inconsistency can cause employees to experience both genuine and perceived threats, such as anticipated interpersonal conflicts or isolation by others (Jehn et al, 1997;Tepper et al, 2011) or events that obstruct them from achieving their goals (Bouckenooghe et al, 2005). Both perceived and actual threats of gains could trigger employees' perceptions of tension and stress (Bai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the emotional support provided by empowering leadership also contributes to the activation of the individual’s emotional energy ( Chow, 2018 ). In addition, from a cultural context perspective, previous studies have confirmed that high power distance has an inhibitory effect on positive work behaviors (e.g., job performance and voice behaviors) ( Bai et al, 2017 ; Zhou and Liao, 2018 ). Empowering leadership can reduce the negative effects of power distance ( Luo and Xiao, 2020 ), stimulating individual vigor.…”
Section: Introductionmentioning
confidence: 93%